Multicultural education values in islamic cultural history: An analysis of the grade XI madrasah aliyah textbook - Diana Lorenza; Mifta Apriliah; Ahmad Ilham; Muhammad Taufiqurrahman; Abdul Nizar (Yayasan Azhar Amanaa Yogyakarta, 2024)
This research aims to look at multicultural values ​​in SKI learning books for class XI Madrasah Aliyah. This research method uses a qualitative approach with methods library research. The results of the research show that in the SKI Madrasah Aliyah learning book, there are multicultural educational values, consisting of tolerance values, democratic values, equality values ​​and justice values. It needs to be instilled in the younger generation so that they are able to internalize and apply multicultural values ​​in everyday life so as to avoid division, forming a character that accepts the diversity around them. The multicultural education curriculum in the Islamic cultural history book at Madrasah Aliyah class The values ​​of multicultural education (tolerance, democracy, equality and justice) have been integrated into the History of Islamic Culture learning curriculum for class a larger multicultural and multireligious community that is consistent with the environment and serves as a role model for students.​​